Development of a STEM Self-Efficacy Scale for Malaysian Primary School Children: A Validity and Reliability Study - Sze, Annie Wong Kai (Animo Repository, 2022)
This study aims to examine the psychometric properties of the Malay language version of the STEM Efficacy for Children Scale (SECS). This initiative involved 389 primary school children aged 10–11 in Klang Valley, Selangor, Malaysia. Exploratory factor analysis (EFA) was conducted to identify the underlying factors within 16 items in SECS, followed by confirmatory factor analysis (CFA) to determine the model and reliability of the scale. Based on EFA, SECS managed to capture three factors related to STEM, namely, efficacy in learning science and mathematics, as well as efficacy in the application of engineering. SECS obtained a high Cronbach’s alpha index (>0.8), and CFA confirmed that the model provided a good fit for the data collected. The average variance extracted demonstrated that all constructs in the model were >.50, while the composite reliability was >.80. These findings verify that the scale obtained good internal consistency. Therefore, the analysis proved that SECS is considered reliable and valid in capturing STEM efficacy among primary school children. The scale is expected to offer useful insights for educators, schools, and the government in their policy planning and execution concerning STEM teaching and learning at the primary school level.